Mark's memory resources and the controversy stories (Mark 2:1-3:6) : an application of the frame theory of cognitive science to the Markan oral-aural narrative - Park, Yoon-Man. (Linguistic Biblical Studies, 2010)
This book is a study of the New Testament using the insights of modern linguistics. Its principal concern, above all, is to examine how the Gospel of Mark, produced in an oral-aural culture, may be illuminated by frame theory from cognitive linguistics, a linguistic theory in which the meaning of a word, phrase, clause, sentence, paragraph and thematic unit can only be properly understood against the background of a particular body of knowledge and assumptions. The reason this theory is particulary useful for understanding Mark's ancient text is because as an oral-aural narrative it heavily relies on human memory (cognitive) resources; and so the cognitive theory leads us into a better understanding of ways in which the text is communicated in terms of cognitive processing.